2007
DOI: 10.1016/j.learninstruc.2007.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external scripts in computer-supported collaborative inquiry learning

Abstract: We investigated how differently structured external scripts interact with learners' internal scripts concerning individual knowledge acquisition in a Web-based collaborative inquiry learning environment. 90 students from two secondary schools participated. Two versions of an external collaboration script (high vs. low structured) supporting collaborative argumentation were embedded within a Web-based collaborative inquiry learning environment. Students' internal scripts were classified as either high or low st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
4
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 44 publications
7
135
4
4
Order By: Relevance
“…Future research should focus on experimental manipulations of the moderator variables. In particular, because the optimal script level is likely to be highly dependent on the learners' prior internal scripts (Fischer et al 2013), future research should track the effectiveness of CSCL scripts at different script levels in relation to the learners' prior internal scripts (Kollar et al 2007;Rienties et al 2012). Furthermore, the studies included in this meta-analysis only rarely report data on the actual degree of transactivity of the learners' collaborative activities (Jeong and Joung 2007;Noroozi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should focus on experimental manipulations of the moderator variables. In particular, because the optimal script level is likely to be highly dependent on the learners' prior internal scripts (Fischer et al 2013), future research should track the effectiveness of CSCL scripts at different script levels in relation to the learners' prior internal scripts (Kollar et al 2007;Rienties et al 2012). Furthermore, the studies included in this meta-analysis only rarely report data on the actual degree of transactivity of the learners' collaborative activities (Jeong and Joung 2007;Noroozi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One-of several possibleexplanations for this finding might be that many learners in the studies included in the present meta-analysis may have had very low prior collaboration skills, which would make them good candidates for scriplet level CSCL scripts. Rather poor collaboration skills have indeed been reported in a number of studies on CSCL scripts as a justification for the introduction of CSCL scripts in the first place (e.g., Kollar et al 2007;Stegmann, Weinberger, and Fischer 2007;Rummel, Spada, and Hauser 2009).…”
Section: Moderators Of the Effectiveness Of Learning With Cscl Scriptsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this special issue, a number of scaffolding techniques have been described and/or studied (e.g., observation-based learning, see Van Steendam et al, THIS ISSUE; a-posteriori reflection forms, see Gielen et al, THIS ISSUE). Here as well, a cross-link to research on collaborative learning might be fruitful, as systematic approaches to scaffolding and scripting as well as empirical studies evaluating these forms of support can be found (Kollar, Fischer, & Slotta, 2007;Quintana et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have pointed to certain reasons for these failures, such as unevenly divided work tasks (Strijbos & De Laat 2010), the poor working methods of individual group members (e.g. problems in argumentation) (HĂ€mĂ€lĂ€inen & HĂ€kkinen 2010;Kollar, Fischer & Slotta 2007), problems in skills to regulate learning (JĂ€rvelĂ€ & JĂ€rvenoja 2011), fragile group dynamics (Kreijins, Kirschner, Jochems & Buuren 2007), weak teamwork strategies (Hadwin & JĂ€rvelĂ€, 2011), the inappropriate use of learning resources (Arvaja 2007;Jeong & Hmelo-Silver 2010) or the lack teachers to inspire and orchestrate learning processes (Arvaja, HĂ€mĂ€lĂ€inen & Rasku-Puttonen 2009). Thus, although technology has rapidly advanced, the challenges of collaborative learning remain.…”
Section: Introductionmentioning
confidence: 99%